SIGNIFICANCE OF DOPPLER RI AND SYSTOLIC PEAK OF BREAST CARCINOMA LESIONS SEEN ON MAMMOGRAPHY - Sehrish Waqar (Army Medical College Rawalpindi, 2021)
Objective: To analyze the significance of doppler ultrasound and resistive index (RI) and systolic peak to find the breast Carcinoma lesions seen on mammography.